Gnosticism, Platonism and the late ancient world : essays in honour of John D. Turner - Turner, John Douglas.; Corrigan, Kevin.; Rasimus, Tuomas. (Nag Hammadi and Manichaean Studies, 2013)
This Festschrift honors the life and work of John D. Turner (Charles J. Mach University Professor of Classics and History at the University of Nebraska at Lincoln) on the occasion of his 75th birthday. Professor Turner's work has been of profound importance for the study of the interaction between Greek philosophy and Gnosticism in late antiquity. This volume contains essays by international scholars on a broad range of topics that deal with Sethian, Valentinian and other early Christian thought, as well as with Platonism and Neoplatonism, and offer a variety of perspectives spanning intellectual history, Greek and Coptic philology, and the study of religions.